HUBUNGAN ANTARA PENYAKIT SISTEMIK PADA LANSIA PRIA DENGAN DISFUNGSI EREKSI - Ghofar, Abdul; -, Ashari (Eduhealth, 2010)
AbstractMen who have age for, 40 to 80 years, 52% of them consider that sexual activity is the importan thing while men who have erectile dysfunction at age from 40 to 60 years, and more than 60 years old are 75% suffer erectile dysfunction. Sexual disfunction have because of disorder organ, it’s decrease of blood circulation to screw which is influence by some factors they are: hypertension, diabetes mellitus, age over than 40 years old. This research is used to know the relationship between sistemic illness to old age men and erectile dysfunction. The data was got on July at PWRI Kabuh Kabuh district, Jombang regency. The design of research use analisitic survey with cross sectional. Population in this research are 70 old age / responden, by using total sampling as a technique of sampling to get the incluse criteria. Measuring for is used by researcher to measure glucose in their blood with random sampling. While hypertension use sistolic pressure. Instrumen in this research is a questionare, it is used measure the erectile dysfunction with EHS scale. Data analysist used mann Whitney and Spearman rank as statistic experiment. The resulth of research show that there is relationship between sistemic illness and erectile dysfunction, with odds ratio old age suffer erectile dysfunction old sistemic illness 5 time higher than men with40-60 year old. Based on the result of research above sistemic illness at old age can cause dysfunction to sexual activity and it also can have influential in the have hold life. To avoid these risk, old age people or suffer of sistemic illness can be given explanation about erectile dysfunction. Avoid condusing pills or medicine life style that can the caused of disfunction erection, for example dringking alcohol other erectile dysfunction pills.Key word : sistemic illness, diabetes mellitus, hypertension, old age, erectile dysfunction